Effective Activation of BKCa Channels by QO-40 (5-(Chloromethyl)-3-(Naphthalen-1-yl)-2-(Trifluoromethyl)Pyrazolo [1,5-a]pyrimidin-7(4H)-one), Known to Be an Opener of KCNQ2/Q3 Channels - Wei-Ting Chang; Sheng-Nan Wu (MDPI AG, 2021)
QO-40 (5-(chloromethyl)-3-(naphthalene-1-yl)-2-(trifluoromethyl) pyrazolo[1,5-a]pyrimidin-7(4H)-one) is a novel and selective activator of KCNQ2/KCNQ3 K+ channels. However, it remains largely unknown whether this compound can modify any other type of plasmalemmal ionic channel. The effects of QO-40 on ion channels in pituitary GH3 lactotrophs were investigated in this study. QO-40 stimulated Ca2+-activated K+ current (IK(Ca)) with an EC50 value of 2.3 μM in these cells. QO-40-stimulated IK(Ca) was attenuated by the further addition of GAL-021 or paxilline but not by linopirdine or TRAM-34. In inside-out mode, this compound added to the intracellular leaflet of the detached patches stimulated large-conductance Ca2+-activated K+ (BKCa) channels with no change in single-channel conductance; however, there was a decrease in the slow component of the mean closed time of BKCa channels. The KD value required for the QO-40-mediated decrease in the slow component at the mean closure time was 1.96 μM. This compound shifted the steady-state activation curve of BKCa channels to a less positive voltage and decreased the gating charge of the channel. The application of QO-40 also increased the hysteretic strength of BKCa channels elicited by a long-lasting isosceles-triangular ramp voltage. In HEK293T cells expressing α-hSlo, QO-40 stimulated BKCa channel activity. Overall, these findings demonstrate that QO-40 can interact directly with the BKCa channel to increase the amplitude of IK(Ca) in GH3 cells.